2007
DOI: 10.1038/sj.pcan.4500983
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome for lymph node-positive prostate cancer

Abstract: Although the number of men with lymph node-positive prostate cancer has declined, it is still significant and the challenge remains on how best to treat these patients. Only long-term follow-up can give a true indication of the outcome in prostate cancer. We evaluated our experience in treating lymph node-positive prostate cancer with a median follow-up of 10.2 years. The overall 5-year survival was 78% and the 10-year survival was 56%. Length of tumor control depends on the type of treatment given. Adding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the current case, hormone therapy was selected as the initial treatment because lymph node metastasis was present at the time of diagnosis. Swanson et al reported the five-year and 10-year survival rates of lymph node-positive prostate cancer were 78% and 56%, respectively [ 8 ]. Our patient is still alive 25 years after the initial diagnosis and is not currently receiving any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, hormone therapy was selected as the initial treatment because lymph node metastasis was present at the time of diagnosis. Swanson et al reported the five-year and 10-year survival rates of lymph node-positive prostate cancer were 78% and 56%, respectively [ 8 ]. Our patient is still alive 25 years after the initial diagnosis and is not currently receiving any treatment.…”
Section: Discussionmentioning
confidence: 99%